Handbook on the Law of War for Armed Forces - Mulinen, Frederic de (Geneve : International Comittee of the Red Cross, 1987)
Main international treaties on the law of war
Part 1. Terms of reference
Section 1.1 The law of war and armed forces
Chapter A The law of war
Chapter B Law types
Chapter C Legal position of states
Chapter D Application of the law of war
Chapter E Summary rules for non-international armed conflict
Chapter F Armed forces under the law of war
Chapter G The law of war as a code of conduct and behaviour for armed
Section 1.2 Basic categories of persons and objects
Chapter B Civilian persons
Chapter C Military objectives
Chapter D Civilian objects
Section 1.3 Specifically protected persons and objects
Chapter B Military medical service
Chapter C Civilian medical service
Chapter D Religious personnel and objects
Chapter E Civil defence
Chapter F Cultural objects and places of worship in general
Chapter G Marked cultural objects
Chapter H Works or installations containing dangerous forces
Chapter I Demilitarized zones
Section 1.4 War victims
Chapter A Prisoners of war
Chapter B Wounded, sick, Shipwrecked
Part 2. Control of armed conflict
Section 2.1 Evolution of a conflict
Chapter A Beginning of an armed conflict
Chapter B Escalation of an armed conflict
Chapter C Deescalation and end of an armed conflict
Section 2.2 Preparatory measures in peace-time
Chapter A Strategic measures
Chapter B Executive and administrative measures
Section 2.3 Control during an armed conflict
Chapter C Fundamental protection
Chapter D Basic categories of persons and objects
Chapter E Specifically protected persons and objects
Chapter F War victims
Chapter H Action of intermediaries
Chapter I Duty and action of neutral states
Section 2.4 Measures after an armed conflict
Chapter A Restoring normal conditions
Chapter B Repatriation and release of persons and objects
Chapter C Missing and dead persons
Part 3. Command responsibility
Section 3.1 General responsibility
Chapter A Overall responsibility in military operations
Chapter B Responsibility of every commander
Section 3.2 Law of war training
Chapter A Training principles
Chapter B The law of war instructor
Chapter C Main training levels and categories
Chapter D Reference documents
Chapter A Organization principles
Chapter B Operational and geographical context
Chapter C Specifically protected persons and objects
Chapter D Multinational forces and problems
Chapter E Cooperation with civilian authorities
Section 3.4 Specific circumstances
Chapter A Warfare between dissimilar forces
Chapter B Action in an unusual environment
Chapter C Unusual supply and evaluation circumstances
Part 4. Exercise of command
Section 4.1 The mission
Section 4.2 Elements for decision making
Chapter A Search for information
Chapter B Precautions required by the law of war
Chapter C Tactical siuation
Chapter D Military necessity
Section 4.3 Decision making
Chapter A Time factor
Chapter D Missions to subordinates
Chapter E Coorperation with civilian authorities
Section 4.4 Control of execution
Chapter A Control principles
Chapter B Adjustments during execution
Part 5. Conduct of operations
Section 5.1 Conduct of operations in general
Chapter A Conduct principles
Chapter B Information needed
Chapter C Means of combat
Chapter D Methods of combat
Chapter E Deception effects anticipated
Chapter F Axclution zones and similar areas
Chapter G Specifically protected objects
Chapter H Protected zones
Chapter I Cooperation with civilian authorities
Section 5.2 Conduct of attack
Section 5.3 Conduct of defence
Section 5.4 Movements and locations
Part 6. Behaviour in action
Chapter A Combat principles
Chapter B Foreign ships
Chapter C Foreign aircraft
Chapter D Exclusion zones and similar areas
Chapter F Protected zones
Chapter G Search for victims of combat
Chapter H Capture of victims of combat
Section 6.2 Captured persons and objects
Chapter A Enemy combatants
Chapter B Wounded, sick, shipwrecked
Chapter D Enemy military medical personnel
Chapter E Enemy military religious personnel
Chapter F Enemy military objects
Section 6.3 Non-hostile contacts with the enemy
Chapter A Unilateral measures
Chapter B Interruption of combat
Section 6.4 Measures of combat
Chapter A Military measures
Chapter B Cooperation with civilian authorities
Section 7.1 Conduct of transportation
Chapter A Principles for military transportation
Chapter B Separate military, medical and civilian transportation
Chapter C Joint military, medical and/or civilian transportation
Chapter D Cooperation with civilian authorities
Section 7.2 Evaluation of captured persons and objects
Chapter A Supply principles
Chapter B Medical supply
Chapter C Supply of religious objects
Section 7.4 Medical transportation
Chapter A Medical transportation principles
Chapter B Medical transportation on land
Chapter C Medical transportation at sea
Chapter D Medical transportation by air Part 8. Rear areas
Section 8.1 Logistic bases
Chapter A Logistic principles
Chapter B Military supply and maintenance bases
Chapter C Military medical service bases
Section 8.2 Treatment of captured persons and objects
Chapter B Wounded and sick
Chapter C Death of prisoners of war
Section 8.3 Civil affairs
Chapter A Cooperation with civilian authorities
Chapter B Foreign inhabitants
Chapter C Civil affairs in free foreign territory
Section 8.4 Penal affairs
Chapter A Breaches of the law of war
Chapter B Judicial proceedings
Chapter C Prosecution of prisoners of war
Chapter D Prosecution of foreign inhabitants
Section 9.1 Law of occupation
Section 9.2 Particular provisions on occupation
Chapter B Situation of the civilian population
Chapter C Movements of civilian persons
Chapter D Security measures against inhabitants
Chapter E Penal affairs
Section 9.3 Control of occupation
Chapter B Measures of the occupying power
Chapter C Measures of the authorities and inhabitants of the occupied
Section 9.4 Combat actions in occupied territory
Section 10.1 Law of neutrality
Section 10.2 Particular provisions on neutrality
Chapter A Areas of belligerent operations
Chapter B Access to neutral spece in general
Chapter C Temporary access to neutral space
Chapter D Internment of belligerent armed forces
Section 10.3 Control og neutrality
Chapter B Measures of the neutral state
Chapter C Measures of belligerent parties
Section 10.4 Combat actions in neutral space
Annex 1 Particular provisions on specific weapons
Section 3. Land mines and similar
Chapter B Conditions for permitted use
Section 4. Incendiary weapons
Section 5. Anti-ship mines
Section 1. Individual identity documents
Chapter A Identity cards
Chapter B Identity discs
Chapter D Recommended additional data on identity card
Section 2. Distinctive signs
Section 3. Distinctive signals
Chapter B Distinctive medical light signal
Chapter C Distinctive medical radio signal
Chapter D Distinctive medical radar signal
Chapter E Distinctive medical underwater acoustic signal
Chapter F Other signals
Law of war: Summary for commanders
Law of war: Rules for behaviour in action
Law of war: Training programme
Essentials of the law of war. -- [1987]
Keywords: War (International law); Armed forces; Armed conflict; International law; LAW OF WAR